Canada, the Antarctic and the Madrid Protocol - Adams, Peter (ARCTIC, 2003)
The House of Commons of Canada passed Bill C-42, An Act respecting the protection of the Antarctic Environment, in June 2003. By it, Canada ratifies the Protocol on Environmental Protection to the Antarctic Treaty (the "Madrid Protocol"), which designates Antarctica as a natural reserve, devoted to peace and science. Through this legislation, Canada will have the legal instruments to manage and monitor its citizens and others on Canadian projects in the Antarctic with respect to the environmental codes of conduct established by the Madrid Protocol. Canadians have been involved in Antarctica since the first overwintering at the turn of the 19th century. The level of activity, over the years and today, is much greater than most people think. The Arctic Institute of North America, established in the 1940s, has always had an interest in both polar regions; its Act of Parliament refers to both hemispheres. . The Antarctic Treaty of 1961 establishes that Antarctica shall be used for peaceful purposes only. It prohibits military activity, nuclear tests, and radioactive waste disposal. It promotes international cooperation in research and suspends all sovereignty claims. The Antarctic Treaty System includes the Antarctic Treaty itself, the Convention for the Conservation of Antarctic Seals (CCAS, 1972), the Convention on the Conservation of Antarctic Marine Living Resources (CCAMLR, 1980), and the Protocol on Environmental Protection to the Antarctic Treaty (1991), also known as the Madrid Protocol. . Canada acceded to the Antarctic Treaty and the CCAMLR in 1988 and to the CCAS in 1990. The Madrid Protocol entered into force in 1998, ratified by 29 nations. Canada signed it (agreed to it in principle) in 1991, but did not ratify it. Bill C-42 . is summarized as follows: The purpose of this enactment is to protect the Antarctic environment, particularly by implementing the Protocol on Environmental Protection to the Antarctic Treaty. This enactment provides a permitting regime that gives the Minister the necessary powers ...